Research on Political Culture: Approaches from the Colombian Educational Context - Sabogal Muñoz, Erika Constanza; Escobar Rincón, Liliana del Pilar (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2022)
The document is based on an ongoing investigation and presents the balance of the investigations carried out in Colombia on political culture and education. The studies are grouped from three trends related to: 1. The historical formation of political culture and education. 2. Political culture from participatory and democratic citizenship. 3. Political culture and its relationship with violence and peace, which allow mapping the theoretical methodological orientations on the subject and the projections for future research.